Polymethoxyflavones from citrus inhibited gastric cancer cell proliferation through inducing apoptosis by upregulating RARβ, both in vitro and in vivo. (December 2020) - Wang, Yue; Chen, Yunyi; Zhang, He; Chen, Jiebiao; Cao, Jinping; Chen, Qingjun; Li, Xian; Sun, Chongde
Abstract: In order to discover the active anti-tumor ingredients during the flavonoids separation process of Ougan ( Citrus reticulata cv. Suavissima ), gastric cancer cell lines including AGS, BGC-823, and SGC-7901 were employed to evaluate the proliferation inhibition abilities of Ougan extracts, flavanone components, polymethoxyflavone components, neohesperidin, nobiletin, tangeretin, and 5-demethylnobiletin. Quantitative real-time PCR was used to detect the expression of three retinoic acid receptor genes, including RARA, RARB, and RARG . Western blot and immunohistochemistry were used to detect protein expressions. The results showed that the polymethoxyflavone components and the PMFs monomers inhibited the proliferation of three gastric cancer cell lines and induced apoptosis. The mechanism exploration found that PMFs up-regulated the expression of the RARB gene selectively and activated the Caspase3, 9, and PARP1 proteins. In addition to 5-demethylnobiletin, other PMFs also upregulated the expression of cleaved Caspase8. The mechanism was preliminarily verified by a RARβ inhibitor AGN 193109. Moreover, a nude mice tumor xenograft model confirmed the tangeretin could exhibit in vivo anti-tumor effect through inducing apoptosis and upregulating RARβ protein. All result suggested that tangeretin may be a potentially novel, safe and effective drugs with less toxicity and lesser side effects for gastric cancer therapeutics. Highlights: The activities of inhibiting gastric cancer cells were evaluated in the ingredients of various stages in the isolation and purification of Ougan fruit. PMFs induced apoptosis of gastric cancer cells through RARβ, both in vitro and in vivo . Caspase pathway was involved in PMFs-induced apoptosis of gastric cancer cells.